-6+12=3x-2(x-7)

Simple and best practice solution for -6+12=3x-2(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+12=3x-2(x-7) equation:


Simplifying
-6 + 12 = 3x + -2(x + -7)

Combine like terms: -6 + 12 = 6
6 = 3x + -2(x + -7)

Reorder the terms:
6 = 3x + -2(-7 + x)
6 = 3x + (-7 * -2 + x * -2)
6 = 3x + (14 + -2x)

Reorder the terms:
6 = 14 + 3x + -2x

Combine like terms: 3x + -2x = 1x
6 = 14 + 1x

Solving
6 = 14 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + -1x = 14 + 1x + -1x

Combine like terms: 1x + -1x = 0
6 + -1x = 14 + 0
6 + -1x = 14

Add '-6' to each side of the equation.
6 + -6 + -1x = 14 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = 14 + -6
-1x = 14 + -6

Combine like terms: 14 + -6 = 8
-1x = 8

Divide each side by '-1'.
x = -8

Simplifying
x = -8

See similar equations:

| 2/3r | | y+7-4(-3y-1)=3(y-1) | | 2x^2-5x^2-12x+30= | | 3xy^2+6y^2+40xy+80y-28x-56=0 | | -5s=5-4s | | 8=5/x-8 | | 6x-12=18x+6-12x | | -154=-5(8+4x)+x | | (6y-7)=-1 | | 8(1/4x-1/4) | | -82=5x-2 | | -6=-n | | 18q-19=12-18+19q | | 2x-6x-6=90 | | -6=n | | 4+4k=-8+k | | -300=-20p | | (4t-8)=20 | | -8n-5n=26 | | 20=-n+6n | | p=15-3Qs | | 910x-12=23 | | -13z+2=-14z+20 | | 24/4x3 | | 2(r+1)-r=-2+4 | | 103x+34=52 | | -3y+4=10 | | .87/1 | | 9/2z-7/3=41/6 | | -5-5j=-4j | | K-14=-18 | | -54=16x+312 |

Equations solver categories